Multiple Sclerosis with Limited Treatment Options: A Case Report on Azathioprine as an Alternative Therapy - Nicholas Ciarico; Kennytha Yoesdyanto; Iglesias Owen (Lumina : Indonesian Journal of Neurology, 2026)
Introduction: Multiple sclerosis (MS) is a chronic immune-mediated disease affecting the central nervous system, characterized by demyelination and progressive disability. Estimated prevalence in Indonesia is approximately 0.01 per 100,000 population. Treatment includes managing acute relapses with corticosteroids and DMT to prevent relapses and further disability. Immunosuppressants such as azathioprine are often used in Indonesia as a more accessible and affordable alternative to standard DMTs. Case Presentation: A 30-year-old woman presented to neurology outpatient with history of progressive bilateral lower limb weakness since 2019, accompanied by urinary dysfunction and numbness below abdominal region. Neurological examination revealed paraparesis of lower limbs, hyperreflexia, positive bilateral Babinski signs, hypoesthesia below T10. Brain MRI demonstrated demyelinating lesions in the corpus callosum, bilateral periventricular white matter, and subcortical frontal and parietal lobes, forming a Dawson’s finger pattern. Spinal MRI revealed a demyelinating lesion at the T11 level. Cerebrospinal fluid (CSF) analysis showed type 2 oligoclonal bands. The patient was diagnosed with multiple sclerosis and treated with intravenous methylprednisolone and azathioprine as maintenance. Discussion: The clinical presentation, characteristic MRI findings, and positive oligoclonal bands supported the diagnosis of multiple sclerosis. Although azathioprine is not considered a first-line DMT, it remains a practical treatment option where access to approved therapies is limited. Conclusions: This case highlights the importance of integrating clinical, radiological, and CSF findings in diagnosing multiple sclerosis. Treatment should be individualized according to the patient's clinical condition and available healthcare resources, while improving access to evidence-based DMTs remains an important goal. Keywords: Multiple Sclerosis, Azathioprine, Demyelination, Oligoclonal Bands, Dawson’s Fingers